An Analysis of Gamification in Boosting Training Effectiveness: The Mediating Role of Engagement - Vitriawaty; Paula Lukita; Edwin Ibnu Margani; Tengku Mohd. Khairal Abdullah (Sekolah Tinggi Manajemen IPMI, 2026)
This study explores how gamification influences the effectiveness of training in a corporate middle management program. Based on Social Cognitive Theory (SCT), it aims to fill the mechanistic gap by proposing and empirically testing a mediation model to understand how gamification works, focusing on whether its impact is mediated through participant engagement. The study used a quantitative, explanatory survey design. Data was gathered from 214 participants in the